The Application of Gamification in Online Learning: Case Studying Mobile Apps - Dani Novita Pratiwi, Wahyu Budianto , Gunawan Wang, Emil Robert Kaburuan (International Journal of Control and Automation, 2020)
Technological developments have impacted various systems in life, including in the games industry, which makes educators more creative in designing their learning processes. Gamification is a learning approach using elements in the game that aims to motivate students in the learning process and maximize the feeling of enjoying and binding on the learning process. In addition, this media can be used to attract students’ interests and encourage them to continue learning. In the learning process using gamification, given certain alternatives that can make the learning process more interesting, fun and effective. So that despite using game mechanics, the learning process must be made more fun, building attachments without being realized by students